IL-35, IL-37, and IL-38 in acute pancreatitis: proposed immunopathogenic mechanisms and therapeutic potential - Yan, Hailong; Dang, Xingbo; Du, Gongliang; Ma, Longyang; Dai, Wei; Bao, Shisan; Huang, Xiujuan (Frontiers in Immunology, 2026)
Acute pancreatitis (AP) is driven by premature enzyme activation, pancreatic tissue injury, and dysregulated immune responses. IL-35 and IL-37 are key anti-inflammatory mediators whose dynamic regulation influences disease severity. Circulating IL-35 is typically upregulated in AP, functioning through STAT1/STAT4 signalling to suppress effector T-cell proliferation, inhibit Th1/Th17 differentiation, and promote expansion of regulatory T and B cells, thereby limiting pro-inflammatory cytokine release (e.g., TNF, IL-6, IL-17) and reducing local and systemic inflammation. In contrast, IL-37 is often downregulated early in AP, impairing its ability to suppress NF-κB and MAPK signalling, restrain dendritic cell and macrophage activation, and reduce gasdermin D (GSDMD)-mediated pyroptosis. Experimental restoration of IL-37 diminishes neutrophil and macrophage infiltration, mitigates pancreatic necrosis, and modulates STAT signalling. The interplay of upregulated IL-35 with insufficient IL-37, within a broader cytokine network, emphasises a compensatory yet incomplete anti-inflammatory response. IL-38, although mechanistically promising, has not yet been characterised in human or animal AP models, and its clinical translation remains hypothetical. These insights suggest that clinical strategies—such as recombinant IL-37 therapy, IL-35 modulators, or combination cytokine-targeted interventions—may restore immune homeostasis and improve outcomes in AP.